Challenges in the Korean Medical System after the End of the MERS That Hit Korea In 2015 - Kim, Ah-Hyeon; Shim, Youn-Soo; Park, So-young; An, So-Youn (International Journal of Psychosocial Rehabilitation, 2020)
Background/Objectives: Middle East Respiratory Syndrome(MERS) is caused by the MERS-Korona virus, a type of beta-corona virus, is a serious respiratory disease with numerous reported. The purpose of this study was to provide a comprehensive review of MERS in Korea in 2015 and use it as basic data for preventing future infectious diseases in Korea.Methods/Statistical analysis: This study was designed by the authority. The research material, after MERS- CoV's declaration of an end, the authorities searched the website of a reputable organization in Korea for a proven report on MERS-CoV.Findings: Of 111 male patients and 75 female patients with laboratory-confirmed MERS-CoV infections between May 20, and July 13, 2015, total 38( 20.4% fatality rate) case died. The most common causes of infection occurred in hospital visits and hospital admissions. 82 (44.1%) patients; 64(34.4%) were patients’ family, caregivers, or visitors; 39(21.0%) were healthcare personnel, and one(0.5%) case was of unknown origin. It was associated with 16 medical institutions, most of them related to medical institutions.Improvements/Applications: Judging by this nature, isolation in the hospital of the initial and estimated superconductors is paramount and is an important criterion for prevention and isolation in the future 'Management and Countermeasures of Infectious Diseases'.